Pengaruh Profitabilitas dan Corporate Social Responsibility terhadap Nilai Perusahaan pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2022 - Alfatihah, Muhamad Dani Alif; Kartini, Tina; Nurmilah, Risma (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study aims to determine the effect of corporate social responsibility and intellectual capital on the company's financial performance. The variables used in this study are the Effects of Profitability and Corporate Social Responsibility on Company Value Study of Mining Companies Listed on the Indonesia Stock Exchange for the 2018 – 2022 period. This research was conducted using a quantitative method with an associative approach. The population in this study is the annual reports of mining companies listed on the Indonesian stock exchange 2018-2022 of 10 companies and a sample of 50 company annual reports is taken. In this research, the sample was taken using purposive sampling technique. Data collection techniques using secondary data. The data analysis technique used is descriptive statistical test, classical assumption test, multiple linear analysis, and hypothesis testing. The results of this study indicate: the independent variables are profitability and corporate social responsibility while the dependent variable is company value. The results of this study indicate that profitability influences firm value, corporate social responsibility variable has a significant effect on firm value. Profitability and corporate social responsibility have a simultaneous effect on company value. So it can be concluded that profitability and corporate social responsibility has an effect of only 37.9% on company value and the rest is influenced by other factors not examined in this study.